2019
DOI: 10.1088/1755-1315/372/1/012070
|View full text |Cite
|
Sign up to set email alerts
|

Duck Production for Food Security

Abstract: Poultry meat and eggs are one of the most widely consumed animal origin food in various parts of the world, across a wide variety of cultures, traditions and religions. In 2016 the duck population (Anas spp.) throughout the world reached 1.24 billion and 1.1 billion (89 percent) were in Asia. The production of meat and duck eggs is still lower than chickens, but ducks make a significant contribution in providing high-quality nutritional food needs. The consumption of duck eggs accounts for around 10-30% of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Salmonella enterica serovar Enteritidis (S. Enteritidis) is the primary Salmonella serovar isolated from poultry eggs, and it is frequently associated with egg-related foodborne disease outbreaks (1,2). Duck consumption is second only to that of chickens in Asian nations (3,4), with duck eggs accounting for an estimated 30% of all egg use in China and Southeast Asia (5). Epidemiological studies suggested S. Enteritidis infections to be commonplace in duck farms and slaughterhouses (6,7), with infected ducks posing a substantial risk as sources of contaminated eggs, vertical S. Enteritidis transmission, and associated environmental damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella enterica serovar Enteritidis (S. Enteritidis) is the primary Salmonella serovar isolated from poultry eggs, and it is frequently associated with egg-related foodborne disease outbreaks (1,2). Duck consumption is second only to that of chickens in Asian nations (3,4), with duck eggs accounting for an estimated 30% of all egg use in China and Southeast Asia (5). Epidemiological studies suggested S. Enteritidis infections to be commonplace in duck farms and slaughterhouses (6,7), with infected ducks posing a substantial risk as sources of contaminated eggs, vertical S. Enteritidis transmission, and associated environmental damage.…”
Section: Introductionmentioning
confidence: 99%
“…Enteritidis) is the primary Salmonella serovar isolated from poultry eggs, and it is frequently associated with egg-related foodborne disease outbreaks ( 1 , 2 ). Duck consumption is second only to that of chickens in Asian nations ( 3 , 4 ), with duck eggs accounting for an estimated 30% of all egg use in China and Southeast Asia ( 5 ). Epidemiological studies suggested S .…”
Section: Introductionmentioning
confidence: 99%
“…Duck is one of the most important poultry for humans. Asia is the most important region for duck meat production (the ratio is 82.2%), followed by Europe with 12.4% [7]. In 2016, there were 1.24 billion ducks in the world and 1.1 billion (the ratio is 89.0%) in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Poultry is a livestock commodity that can be categorized into meat-producing and egglaying ones [1]. Apart from chickens, duck's meat and egg contribute significantly to provide highly nutritional food [2]. Local ducks are classified as the Indian Runner duck breed and are also one of Indonesia's germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…The type of duck widely cultivated in Tanjungpinang City is the Mojosari duck. Female Mojosari ducks are developed as egg layers and the male ones as meat-producer [2]. Nutritious feed application has been proven to improve Mojosari duck productivity [4].…”
Section: Introductionmentioning
confidence: 99%